Effects of combination of low cost oil seed cakes as dietary protein sources for Labeo rohita (Hamilton) fingerling (University Journal of Zoology, Rajshahi University, 2007)
Key words: Oil seed cakes, protein source; Labeo rohita; fingerling Univ. j. zool. Rajshahi Univ. Vol.24, 2005. pp. 11-16